THE POWER OF TRANSFORMATIONAL LEADERSHIP IN REBUILDING THE SOCIETY REFLECTED ON ORWELL’S ANIMAL FARM - Andi Farid Baharuddin; Mardiani Mardiani (UIN Alauddin Makassar, 2021)
Leadership is a unique ability that only a few people have. It can influence and motivate people to reach the organizational goal. Leadership style is precious to be applied to any ruler. Therefore, this article aims explicitly to elaborate how transformational leadership, possessed by Snowball as the Main Character, rebuilt the animal society on a farm owned by Mr. Jones. In examining this case above, the researcher applies the Animal Farm novel as the research data source. The methodology applied in this research is a descriptive qualitative method that used the technique of data collection, the technique of data analysis, and the technique of data validation. Furthermore, in analyzing the case, the writer elaborates it with transformational leadership theory elaborated by Charis (2020) and one of the literary theories elaborated by Abrams in Teeuw (1984) as guidance to analyze the Character portrayed in the work. The results show that transformational leadership successfully rebuilt society, particularly in educating society and in triggering society to operate the machine for them.